Regional Odontodysplasia with Generalised Enamel Defect - A. M. Al-Mullahi; K. J. Toumba (Hindawi Limited, 2016)
Regional odontodysplasia (ROD) is uncommon developmental anomaly, which tends to be localised and involves the ectodermal and mesodermal tooth components. A five-year-old female was referred to Department of Child Dental Health at the Leeds Dental Institute regarding malformed primary teeth. On examination 64, 74, and 72 had localised hypomineralized enamel defect. The crown of 55 was broken down with only the root remaining below the gingival level. 54 has a yellowish brown discolouration with rough irregular surface. The upper anterior teeth show mild enamel opacity. Radiographically, 55 and 54 had thin radioopaque contour, showing poor distinction between the enamel and dentine and the classic feature of a wide pulp chamber. 15, 16, and 17 were developmentally delayed and were displaying the characteristic "ghost appearance." Comprehensive dental care was done under local anaesthesia and it included extraction of the primary molars affected by ROD, stainless steel crown on 64, and caries prevention program. Fifteen months following the initial assessment the patient's oral condition remains stable and she is under regular follow-up at the department. Paediatric dentists should be aware of this anomaly as it involves both dentitions and usually requires multidisciplinary care.